Travel motivation, values, personality and well-being - Mazni Mustapha; Roseni Ariffin; Habibie Ibrahim (Faculty of Psychology and Education, UMS, 2023)
People achieve different levels of satisfaction in their lives depending on what they need from life, perhaps affected by life domains. Biological factors physical health and genetics (biological), behaviour and personality (psychological) as well as family, friends, and socioeconomic (social) are some of the examples in life domains which some people value these factors differently from others. Subjective life satisfaction indicators are based on the elements that an individual considers personally valuable in their own life. Unfortunately, when the whole world is hit by the outbreak of coronavirus at the end of 2019 and many aspects of life such as economy, education, tourism, health and others have been seriously affected . The devastating problems have led to many downturns especially on humans’ subjective wellbeing. The pandemic forces everyone to obey the self-quarantine and social-distancing orders which adversely affect their social well-being. Despite of the vaccinations and standard guidelines of social distancing and working from home, the community however still needs to accept the norm of living with the outbreak as its ability to evolve in order to prepare themselves for endemicity. Therefore, apart from taking care of most sectors, such as economy, health and safety should be emphasized including people’s well-being. Hence, this concept paper intends to investigate specifically on the relationships between subjective well-being and human values, travel motivation, as well as personality. This paper also discusses the Maslow’s hierarchy of needs, whereby individuals will find ways in fulfilling their needs in order to reach the self-actualization phase, including motivation to travel.